2000
DOI: 10.1111/j.1553-2712.2000.tb02067.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Data Sources for Motor Vehicle Crash Characteristic Accuracy

Abstract: Abstract. Objective: To determine the accuracy of police reports (PRs), ambulance reports (ARs), and emergency department records (EDRs) in describing motor vehicle crash (MVC) characteristics when compared with an investigation performed by an experienced crash investigator trained in impact biomechanics. Methods: This was a cross-sectional, observational study. Ninety-one patients transported by ambulance to a university emergency department (ED) directly from the scene of an MVC from August 1997 to April 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Studies aiming to establish causality rely mostly on police accident reports via national crash databases like the National Automotive Sampling System's General Estimates System (NASS-GES) and the Fatality Analysis Reporting System (FARS) (Williams et al, 1995;Chen et al, 2000;Rice et al, 2003;Neyens and Boyle, 2008). However, these analyses may be limited in several aspects, including over assignment of culpability to teens because of their age, inconsistency of information collected on accident reports (Grant et al, 2000), and an inability to elucidate the actual causal chain of events of the crash. While two studies with enhanced designs have advanced the literature by providing more detail on specific actionable factors (Mcknight and Mcknight, 2003;Braitman et al, 2008), these studies are not without important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies aiming to establish causality rely mostly on police accident reports via national crash databases like the National Automotive Sampling System's General Estimates System (NASS-GES) and the Fatality Analysis Reporting System (FARS) (Williams et al, 1995;Chen et al, 2000;Rice et al, 2003;Neyens and Boyle, 2008). However, these analyses may be limited in several aspects, including over assignment of culpability to teens because of their age, inconsistency of information collected on accident reports (Grant et al, 2000), and an inability to elucidate the actual causal chain of events of the crash. While two studies with enhanced designs have advanced the literature by providing more detail on specific actionable factors (Mcknight and Mcknight, 2003;Braitman et al, 2008), these studies are not without important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al [5] reported an increase in the frequency of speeding, driver error, and single-vehicle crashes among teens in fatal crashes with peer passengers (compared with solo drivers), and Aldridge et al [8] found that crash-involved teens carrying passengers were more likely to travel at unsafe speeds compared with those driving alone or with passengers of other ages. However, these studies relied solely on police accident report data, which may not have been collected systematically across jurisdictions, are limited in scope, may overassign culpability to teens because of their age, and may have issues with accuracy [17].…”
mentioning
confidence: 99%
“…Ninety-one patients transported by ambulance to an emergency department directly from the scene of a MVC were analysed. Agreement using k between the crash investigation and different data sources was 0.58 for the police report, 0.33 for the ambulance report and 0.49 for the emergency department report (Grant et al, 2000). Similar problems exist in self-reported MVC.…”
Section: Introductionmentioning
confidence: 88%